A critique of Malpass's argument against Supervaluationism. Issue 1 (8th November 2022) - De Florio, Ciro; Frigerio, Aldo
Abstract: Supervaluationism is one of the most discussed approaches to the semantics of future tense sentences in a branching time. In this paper, we consider the criticism advanced by Malpass against Supervaluationism. This criticism relies on the fact that supervaluationists must accept as supertrue disjunctions whose disjuncts are not only supertrue—which supervaluationists are ready to acknowledge—but also not satisfiable. In order to show this, Malpass proposes a formula, F F 1, which shows the existence of a satisfiable disjunction with unsatisfiable disjuncts in supervaluationist models. In reply, we show that formula F F 1 cannot be expressed within a model (whether Ockhamist or supervaluationist) because it quantifies on models. It can be correctly characterised only within a meta‐model that has the resources to quantify on various models. However, once that is done, F F 1 is, for the advocates of Supervaluationism, no more demanding than other disjunctions because it just generalises at the meta‐theoretical level what supervaluationists already acknowledge at the theoretical level.